2007
DOI: 10.1080/08860220701392314
|View full text |Cite
|
Sign up to set email alerts
|

Central Pontine and Extrapontine Myelinolysis after Rapid Correction of Hyponatremia by Hemodialysis in a Uremic Patient

Abstract: Osmotic demyelination syndrome, a well-known entity, is characterized by demyelination in the pons and extrapontine areas. Rapid correction of chronic hyponatremia is its most important cause. This report presents a 52-year-old man with uremia and hyponatremia. Demyelination syndrome developed after the first hemodialysis session. Brain images showed central pontine myelinolysis and extrapontine myelinolysis. This case emphasizes the fact that demyelination syndrome can occur when hyponatremia is corrected too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…Thus, intermittent hemodialysis would be expected to result in a rapid rise in the serum sodium level in cases of severe predialytic hyponatremia. Nonetheless, only two cases of osmotic demyelination syndrome following rapid correction of severe hyponatremia with hemodialysis have been reported [13,14]. In one of these cases [13], the serum sodium concentration increased by 35 mmol/l over 4 days, and in the other case [14], the serum sodium level rose by 21 mmol/l following a single hemodialysis session.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, intermittent hemodialysis would be expected to result in a rapid rise in the serum sodium level in cases of severe predialytic hyponatremia. Nonetheless, only two cases of osmotic demyelination syndrome following rapid correction of severe hyponatremia with hemodialysis have been reported [13,14]. In one of these cases [13], the serum sodium concentration increased by 35 mmol/l over 4 days, and in the other case [14], the serum sodium level rose by 21 mmol/l following a single hemodialysis session.…”
Section: Discussionmentioning
confidence: 99%
“…CPM can develop in the absence of serum sodium fluctuations, with more than one predisposing factor. Chronic alcoholism is the most common reason for developing CPM (6). However, only a small number of cases of CPM following alcohol withdrawal have been reported (8,9); the majority of the cases are associated with normonatremia (10).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 3,000 brains examined postmortem, 15 cases of asymptomatic CPM were evident (5). Kleinschmidt-Demasters et al (6,7) reported that 39.4% of patients of CPM were diagnosed with alcohol poisoning, 21.5% had a history of correcting hyponatremia, and 17.4% received a liver transplantation. Although earlier reports on CPM described very poor outcome with mortality rates as high as 50% in the first 2 weeks after presentation and 90% at 6 months, recent results suggest the decreased mortality mainly due to early diagnosis and improved intensive care treatment (7).…”
Section: Introductionmentioning
confidence: 99%
“…Since then it is not infrequent that many clinicians associate rapid correction of hyponatremia as the sole cause of ODS. Nevertheless, it is now well known that a variety of other medical conditions (where an osmotic shift has not been identified) such as alcoholism, malnutrition, cirrhosis, liver transplantation, hypokalemia, hypophosphatemia, and hypomagnesaemia, AIDS, folate deficiency, psychogenic polydipsia, beer potomania, refeeding syndrome, dialysis disequilibrium syndrome, hyperemesis gravidarum, sepsis, malignancy, lithium toxicity, prolonged diuretic use, and hypoglycemia have also been associated with ODS [6][7][8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis is still to be clearly understood, it is known that rapidly increasing serum osmolality shifts water out of the cells as a response to correct solute imbalance resulting in shrinkage of glial cells that can consequently lead to disruption of the blood-brain barrier allowing inflammatory mediators to enter the central nervous system damaging oligodendrocytes and myelin [4][5][6][7] . Even though ODS has been classically thought to be exclusively secondary to a rapid correction of hyponatremia, it has also been described, even though rarely, in various other situations such as malnutrition, liver transplantation, alcoholism, hypokalemia, hypophosphatemia, AIDS, lithium toxicity, hypoglycemia, and folate deficiency, among others [8][9][10][11][12][13][14][15] . In all cases a growing body of evidence demonstrates that more than sodium per se, the key factor, in ODS pathogenesis, is a rapid change in serum osmoles.…”
Section: Introductionmentioning
confidence: 99%